Common mental disorders among medical students: systematic review and meta-analysis of Brazilian studies - Soares, Silvio José Batista; Fernandes, Cláudia Fernanda Garcez; Tabalipa, Renata; Kogima, Felipe; Jubini, Marcelo Augusto Moreira; Dias, Isabella Martins Vieira; Soares, Victor Emanuel Miranda; Amaral, Severina Silva; Cruz, Michele Santos da; Guerra, Paulo Henrique (São Paulo Medical Journal, 2022)
BACKGROUND: Common mental disorders (CMDs) have been correlated with consequences in different domains of life. OBJECTIVE: To summarize the prevalence rates of CMDs and factors associated with them among students at Brazilian medical schools. DESIGN AND SETTING: Systematic review and meta-analysis of studies developed in Brazilian medical schools. METHODS: In October 2021, searches were carried out in seven electronic databases, in Google Scholar and in reference lists. Observational studies reporting prevalence rates of CMDs among students at Brazilian medical schools were sought. Variables associated with CMDs arising from multivariate regression models were included in the synthesis. A meta-analysis was developed using a random-effects model and the risk of bias was assessed using an instrument developed from previous references. RESULTS: Fourteen original studies were included. The pooled prevalence rate of CMDs among under-graduate students at Brazilian medical schools was 43.3% (95% confidence interval = 38.9% to 47.6%; I2 = 87%; n = 3,927). Among the nine studies in which multivariate analyses were conducted, five showed risk associations between CMDs and medical school-related dissatisfactions, among which the desire to abandon the medical course can be highlighted (n = 3). In three studies, CMDs were associated with sleep indicators. CONCLUSION: Considering that the prevalence of CMDs among medical students is higher than in the general population, we recommend that Brazilian medical schools should give greater attention to this topic, and should enable expansion of care offerings relating to mental health. SYSTEMATIC REVIEW REGISTRATION: Prospective register of Systematic Reviews (PROSPERO) database (CRD42020142184).